Stakeholders’ Roles, Paradigms and Interactions in Conservation Management: A Systematic Review - Gooi, LiangJun; Kusumo, Camelia; Widodo, Johannes (MAJ - Malaysia Architectural Journal, 2023)
This paper attempt to synthesise different articles published regarding conservation management on different heritage sites. It examines the commonality, differences and effectiveness of heritage conservation management in different regions without endorsing bottom-up management as the best approach, providing an insight on the current trend. Articles are chosen via SCOPUS database, using Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) model established by Liberati. These articles are analysed via three models derived from (1) Mitchell’s Stakeholders Identification Theory to analyse stakeholders’ role, (2) Conservation Theory to analyse stakeholders’ paradigms and (3) Wells and Lixinski’s Typology of Community Participation to analyse stakeholders’ interaction. The result displays trends adopted in different regions, providing an insight into attributes affecting conservation management.